2023
DOI: 10.1111/imr.13259
|View full text |Cite
|
Sign up to set email alerts
|

Hijacking homeostasis: Regulation of the tumor microenvironment by apoptosis

Abstract: SummaryCancers are genetically driven, rogue tissues which generate dysfunctional, obdurate organs by hijacking normal, homeostatic programs. Apoptosis is an evolutionarily conserved regulated cell death program and a profoundly important homeostatic mechanism that is common (alongside tumor cell proliferation) in actively growing cancers, as well as in tumors responding to cytotoxic anti‐cancer therapies. Although well known for its cell‐autonomous tumor‐suppressive qualities, apoptosis harbors pro‐oncogenic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 303 publications
(707 reference statements)
0
4
0
Order By: Relevance
“…For instance, gain of chromosome 1q, which harbors the MDM4 gene and occurs in many BCas, was recently shown to be largely mutually exclusive with TP53 mutations, but associated with downregulation of TP53 target genes (60). Moreover, a recent study has shown that TP53 LOH results in genomic instability, which leads to chromosome 13 loss, along with other CNAs, during the progression of pancreatic ductal adenocarcinoma (61). These notions are consistent with our observation that 13q14.2 loss statistically significantly co-occurs with TP53 -inactivating genomic events and support our hypothesis that the loss of 13q14.2 in BCa could be a downstream consequence of initial TP53 pathway-impairing genomic alterations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, gain of chromosome 1q, which harbors the MDM4 gene and occurs in many BCas, was recently shown to be largely mutually exclusive with TP53 mutations, but associated with downregulation of TP53 target genes (60). Moreover, a recent study has shown that TP53 LOH results in genomic instability, which leads to chromosome 13 loss, along with other CNAs, during the progression of pancreatic ductal adenocarcinoma (61). These notions are consistent with our observation that 13q14.2 loss statistically significantly co-occurs with TP53 -inactivating genomic events and support our hypothesis that the loss of 13q14.2 in BCa could be a downstream consequence of initial TP53 pathway-impairing genomic alterations.…”
Section: Discussionmentioning
confidence: 99%
“…While primarily known for its tumor-suppressing effects, apoptosis also has pro-oncogenic properties (64). The pro-oncogenic property is mainly due to its non-cell-autonomous effects, particularly involving the interaction with tumor-associated macrophages in the tumor microenvironment (61, 65, 66). This correlates with our findings that demonstrate the positive impact of 13q14.2 loss on the macrophage populations within the TME.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer is driven by a set of drastic molecular changes that disrupt tissue homeostasis of a specific niche [ 1 , 2 ]. This disruption is rooted in changes in cellular chromatin that alter patterns of gene expression and thereby induce expression of molecules that facilitate cancer progression and interfere with the function of the immune system [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…This is detailed in four of the final chapters of this volume. First, Christopher Gregory details beautifully the complexity of cell death in the cancer context 27 . He details how apoptotic cells and their products (including extracellular vesicles and other factors released by the dying cells) regulate the tumor microenvironment; this includes how responses of the macrophages within solid tumors, either due to direct contact with the apoptotic cells or their released products, lead to reshaping the tumor microenvironment for tumor growth.…”
mentioning
confidence: 99%